Colony membership, division of labor, and genetic relatedness among females of colonies of eustenogaster fraterna (Hymenoptera, Vespidae, Stenogastrinae) - Hashim, Rosli; Francescato, E.; Massolo, A.; Landi, M.; Gerace, L.; Turillazzi, S. (2002)
To compare the social structure of primitively social wasps with that of communal breeding vertebrates, we used a new technique based on micro videocameras applied to the nest envelope to study the organization of behavior in Malaysian colonies of the stenogastrine wasp Eustenogaster fraterna. The reproductive division of labor in this species appears to be different from that reported so far in other species of Stenogastrinae: it is at a very primitive stage because the helpers work less hard and take fewer risks than the egg-layers. Nevertheless, the very low-risk tasks performed by the helpers (nest guarding and supply of abdominal secretion to the young larvae) are important for the colonies. Behavioral characters and ovarian development of the helpers suggest that females are only temporary helpers and that they wait to start their own production of offspring in the hope of inheriting the nest. Females of the same colony can be highly related, but in some colonies we found low-related individuals. The social organization of these wasps resembles that of vertebrate groups with helpers at the den, i.e., in the small number of individuals, the division of labor with limited reproductive inhibition, and the prolonged external work of the reproductive individuals. However, the main drive to sociality in these insects appears to be different, being based mainly on problems connected with short adult life and long immature brood development.